Strategic Belonging: Hindu Identity and Performance in Oman. Issue 4 (2nd October 2022) - Mehta, Sandhya Rao
Abstract: This study focuses on the multiple ways in which the Hindu community in Oman negotiates its religious identity in an Islamic country by strategically using its historic mercantile relations with the ruling families, maximising the use of public-private spaces, and creating and participating in transnational networks as ways to cope with state restrictions. Using Vertovec's notion of 'complexifying complex diasporas, ' this study examines how Hindus, while being publicly 'invisible, ' have been able to possess a continuing cultural platform which is leveraged to acquire opportunities for religious performance. However, challenges to such strategic belonging have been rising rapidly with the rise of right wing Hindu ideology within and outside India. The repercussions of the establishment of a Hindu state in India on its diaspora, particularly in an officially Muslim country, are rife with challenges. Alternative strategies may have to be explored by the community to assert its identity and religious practices, as well as secure its future in Oman.